Multimodality Treatment by FOLFOX plus HIFU in a Case of Advanced Pancreatic Carcinoma. A Case Report - Dimitrov, Dobromir; Andreev, Tihomir; Feradova, Hyuliya; Ignatov, Borislav; Zhou, Kunn; Johnson, Colin; Delijski, Tashko; Gortchev, Grigor; Tomov, Slavcho (JOP. Journal of the Pancreas, 2015)
Context Pancreatic cancer is one of the most aggressive malignant diseases in which the survival rate has not improved in the past 40 years. Case report A fifty-one-year-old male patient with inoperable metastatic pancreatic cancer and low response to chemotherapy with gemcitabine as single therapy underwent palliative high intensity focused ultrasound (HIFU) ablation. Continuing chemotherapy with folinic acid, oxaliplatin and 5-fluorouracil (FOLFOX) was made. Tools, provided by the European Organization for Research and Treatment of Cancer (EORTC) were used to evaluate his quality of life. The Global Health Status improved from 25 to 42 out of 100 and the body mass index (BMI) increased from 14.9 to 18.1 kg/m2. Measured by the visual analog scale, the pain was reduced from 7 to 2 out of 10. Twelve months after the HIFU ablation, CT revealed decreased size of the tumor and liver lesions. Conclusion FOLFOX plus interventional, physical destruction of the primary tumor by HIFU sufficiently improved the quality of life, reduced pancreatic pain and provided better survival in this case. Image: Hyper-echogenic tumor immediately after HIFU ablation.